A new approach to overcome cytotoxic effects of Cu by delivering dual therapeutic ions (Sr, Cu) - Anand, Akrity; Sengupta, Susanta; Galusek, Dušan; Beltrán, Ana M.; Galusková, Dagmar; Boccaccini, Aldo R. (Journal of Trace Elements in Medicine and Biology, 2025)
Introduction: The incorporation of trace elements such as strontium (Sr) and copper (Cu) in the composition of mesoporous bioactive glass (MBG) is widely known to enhance its biological functionality for bone tissue regeneration Methods: Two MBG powders with the composition 80SiO2-11CaO-5P2O5-xCuO/SrO, one doped with 4 mol.% of CuO, the second with 4 mol.% of SrO were blended in the weight ratios of Cu-MBG: Sr-MBG; 100:0, 70: 30, 50: 50, 30: 70 and 0:100 aiming at minimizing Cu to minimize the cytotoxicity of Cu while preserving its antimicrobial activity. The synergistic effects of Sr and Cu ions on bioactivity, cytotoxicity, and antimicrobial activity were studied. Results: Transmission electron microscopy (TEM) examination of Cu-MBG and Sr-MBG showed fringes related to the development of a mesoporous structure. The specific surface area values of the Cu-MBG and Sr-MBG powders were 287 and 349 m2/g, respectively. A characteristic compact layer consisting of particles with platelet-like morphology commonly associated with HAp crystals was confirmed after 7 days soaking in simulated body fluid (SBF). Mouse preosteoblast cells (MC3T3-E1) exhibited higher cell viability when exposed to a 1 % w/v eluate from blended Cu-MBG powders compared to pure Cu-MBG. Notably, the Cu-MBG: Sr-MBG ratio of 30:70 exhibited cell viability of around 85 % at this concentration. A higher cell viability (above 100 %) towards MC3T3-E1 cells was observed for all powders when tested with the 0.1 % w/v eluate. With progressive increase in the amount of Cu-MBG in the blended system the bacterial inhibitory effects were more pronounced. The Cu ions released from Cu-MBG generate hydroxyl ions and increase the pH leading to disruption of the cellular membrane of microbes, resulting in enhanced antimicrobial activity. Conclusion: This newly developed blended system composed of Cu and Sr doped MBGs is expected to be more effective as bioactive filler in comparison to single ion doped MBGs for bone tissue engineering applications.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Antimicrobial properties; Bioactive glasses; Cytotoxicity; Hydroxyapatite; Sol-gel